Algebraically or Geometrically?

Calculus Level 3

lim x 0 ( a sin ( x ) x + b tan ( x ) x ) = ? \displaystyle \lim_{x\rightarrow 0} \left(\ \left\lfloor \dfrac{a\sin(x)}{x} \right \rfloor+\left\lfloor \dfrac{b\tan(x)}{x} \right \rfloor \ \right)= \ ?

Given that a , b a,b are natural numbers.


Try for some more interesting problems of Limits and Derivatives.
a + b 1 a+b-1 a + b a+b a b a-b a + b + 1 a+b+1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Prasun Biswas
Feb 25, 2015

Observing the Maclaurin Series of trigonometric functions, we can conclude that,

x 0 x sin x , x tan x , sin x < x < tan x sin x x 1 , tan x x 1 + a sin x x a , b tan x x b + a , b N x\to 0\implies x\to \sin x~,~x\to \tan x~,~\sin x\lt x\lt \tan x\\ \implies \frac{\sin x}{x}\to 1^-~,~\frac{\tan x}{x}\to 1^+\\ \implies \frac{a\sin x}{x}\to a^-~,~\frac{b\tan x}{x}\to b^+~\forall a,b\in \mathbb{N}

Now, we begin to evaluate the limit using the results obtained.

lim x 0 ( a sin x x + b tan x x ) = lim x 0 ( a + b + ) = lim x 0 ( ( a 1 ) + ( b ) ) = a + b 1 \lim_{x\to 0} \left( \left\lfloor \frac{a\sin x}{x} \right\rfloor + \left\lfloor \frac{b\tan x}{x} \right\rfloor \right)\\ =\lim_{x\to 0} \left( \left\lfloor a^- \right\rfloor + \left\lfloor b^+ \right\rfloor \right)\\ = \lim_{x\to 0} \left((a-1)+(b)\right)\\ = \boxed{a+b-1}


The Maclaurin series for the two trigonometric functions are:

sin x = x x 3 3 ! + x 5 5 ! x 7 7 ! + = i = 0 ( 1 ) i ( 2 i + 1 ) ! x 2 i + 1 tan x = x + x 3 3 + 2 x 5 15 + 17 x 7 315 + = i = 0 ( 1 ) i 2 2 i + 2 ( 2 2 i + 2 1 ) B 2 i + 2 ( 2 i + 2 ) ! x 2 i + 1 \sin x = x-\frac{x^3}{3!}+\frac{x^5}{5!}-\frac{x^7}{7!}+\ldots = \sum_{i=0}^\infty \frac{(-1)^i}{(2i+1)!}x^{2i+1}\\ \tan x = x+\frac{x^3}{3}+\frac{2x^5}{15}+\frac{17x^7}{315}+\ldots = \sum_{i=0}^\infty \frac{(-1)^i2^{2i+2}(2^{2i+2}-1)B_{2i+2}}{(2i+2)!}x^{2i+1}

where B n B_n is a Bernoulli number (defined only for even index).

Moderator note:

Well done. Great use of the inequality sin ( x ) < x < tan ( x ) \sin (x) < x < \tan (x) .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...